Extremadura represented in the media. Intertextuality and stereotypes - Cañamero Alvarado, Mª Cristina (Historia y Comunicación Social, 2014)
The first half of the twentieth century is rich in iconographic manifestations in the mass media, a particular area, Extremadura, becomes iconographic object covers, magazines and documentaries. Three works are key to the expansion of iconographic references: Ruth M. Anderson, In the lands of Extremadura, Luis Buñuel The Hurd: Land Without Bread and Spanish Village: It lives at ancient poverty and faith, W. Eugene Smith. The objective set is to show intertextuality lines containing study images through visual representations.